A escrita do gênero memórias: das práticas sociais contexto de sala de aula - Sousa Neta, Raimunda de (2016)
Currently, the teaching of Portuguese Language in Brazil is guided by the National Curricular Parameters (BRASIL, 1998), which are based on the theory of discursive genres, preconized by mikhail Bakhtin (2015). This theory constitute, undoubtedly, one of the possible alternatives to diminish the difficulty that many students have, concerning the reading and writing skills, since it permits to improve the discursive dominion of the student, making him able to work effectively in the several spheres of communication of the society where he lives in. Thus, the aim of this work, which presents a qualitative approach, with an interventionist and descriptive nature, consisting of a research - action, is to evaluate the extent to which the didactic sequence procedure with the textual genre Memórias can contribute to the improvement of the writing ability of students of the 9th grade of Fundamental Teaching of a public school in João Pessoa city, Paraiba, as well as giving visibility to the memories of the representative social groups of the social cultural universe in which they are inserted. Therefore, the study started from the conception by Bakhtin (2015), which approaches the language as a way of social interaction and production, and by authors who share his ideas about this theme, such as Marcuschi(2008), and Noverraz and Schneuwly (2004); the proposal of didactic sequence by Dolz, Noverraz and Schneuwly(2004); and the studies about Memories of Ecléa Bosi (1998), Jacques Le Goff (1990) and Halbwachs (1990), among others. The analyses of the results show us that the intervention accomplished through the proposed didactic sequence makes it possible, not only to support the student to improve the writing of the Memory gender, as well as to make him know and rescue social cultural values of his comunities, through his memories reminded by people who surround him, which contribute, according to Le Goff.(1990), to the affirmative of the individual and collective identity.